2000
DOI: 10.1177/147323000002800606
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Resistant Tuberculosis at the University Hospital in Gaziantep, South-Eastern Turkey

Abstract: We aimed to determine the present status of drug resistance of Mycobacterium tuberculosis at the Gaziantep University Hospital in south-east Turkey. Data for 1995 to 1999 were retrospectively evaluated with respect to smear-positive cases, first positive culture for Mycobacterium tuberculosis for each patient and drug-susceptibility tests for the major antituberculous drugs. Cultures were done using the Bactec 460 TB method. A total of 106 (40.2%) strains were resistant to at least one drug. Single drug resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 7 publications
1
10
0
1
Order By: Relevance
“…In 2005, Surucuoglu and colleagues reported that the rate of resistance to any anti-TB drugs among 355 isolates of Mycobacterium tuberculosis obtained from western Turkey was 21.1%, while another study found that among the 1,513 TB cases diagnosed in Istanbul, Turkey, in 2005, 19% were resistant to at least one drug (20,25). These rates are similar to the rates of drug resistance found in some of the Eastern European countries that are considered to have the highest drug resistance rates in the world (3). The high drug resistance rate poses a major challenge to the control of TB in Turkey.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…In 2005, Surucuoglu and colleagues reported that the rate of resistance to any anti-TB drugs among 355 isolates of Mycobacterium tuberculosis obtained from western Turkey was 21.1%, while another study found that among the 1,513 TB cases diagnosed in Istanbul, Turkey, in 2005, 19% were resistant to at least one drug (20,25). These rates are similar to the rates of drug resistance found in some of the Eastern European countries that are considered to have the highest drug resistance rates in the world (3). The high drug resistance rate poses a major challenge to the control of TB in Turkey.…”
mentioning
confidence: 68%
“…Although the TB incidence in Turkey has decreased by half since 1985, several studies have shown the proportion of drugresistant TB cases to be higher than the global average (3,5,10,11,20,24,26). In 2005, Surucuoglu and colleagues reported that the rate of resistance to any anti-TB drugs among 355 isolates of Mycobacterium tuberculosis obtained from western Turkey was 21.1%, while another study found that among the 1,513 TB cases diagnosed in Istanbul, Turkey, in 2005, 19% were resistant to at least one drug (20,25).…”
mentioning
confidence: 99%
“…Ülkemizde yapılan çalışmalarda TB izolatlarında en az bir ilaca direnç %15-35 arasında bulunmuştur 15,16 . Bölgemizde yapılan bir çalışmada ilaç direnci %40.2 gibi yüksek bir oranda saptanmıştır (17). Literatürde yapılan TB konusunda yapılan geniş bir taramada izolatlarda ÇİD oranları en yüksek olarak şu ülkelerde bildirilmiştir; Nepal (%48), Gujarat, Hindistan (%34), New York (%30), Bolivya ve Kore ( her biri %15) 18 .…”
Section: Discussionunclassified
“…Hemangiomas usually expansively grow and disrupt the cortex thus they can be misdiagnosed as agressive tumors or infectous processes (4). Mycobacterium tuberculosis infection with drug resistant species is highly prevalent in southeastern Turkey (5). Mycobacterial infection of the thoracic cage is rare and is difficult to discern clinically and on radiographs (6).…”
Section: Introductionmentioning
confidence: 99%